Does the Tacrolimus Trough Level Adequately Predict Drug Exposure in Patients Requiring a High Tacrolimus Dose?. Issue 4 (29th March 2023) - Haverals, Lien; Roosens, Laurence; Wouters, Kristien; Marquet, Pierre; Monchaud, Caroline; Massart, Annick; Abramowicz, Daniel; Hellemans, Rachel
Abstract : Background: Tacrolimus (Tac) has a narrow therapeutic range. Dosing is generally targeted at Tac trough levels ( C 0 ), notwithstanding conflicting reports on the correlation between Tac C 0 and systemic exposure measured by the area-under-the-concentration-over-time curve (AUC). The Tac dose required to meet the target C 0 varies highly among patients. We hypothesized that patients requiring a relatively high Tac dose for a certain C 0 may show a higher AUC. Methods: We retrospectively analyzed data from 53 patients in which a 24-h Tac AUC24 estimation was performed at our center. Patients were divided into those taking a low (≤0.15 mg/kg) or high (>0.15 mg/kg) once-daily Tac dose. Multiple linear regression models were used to investigate if the association between C 0 and AUC24 changes according to dose level. Results: Despite the large difference in mean Tac dose between the low- and high-dose group (7 versus 17 mg/d), C 0 levels were similar. However, the mean AUC24 was substantially higher in the high-dose group (320 ± 96 h·μg/L versus 255 ± 81 h·μg/L, P < 0.001). This difference remained significant after adjusting for age and race. For a same C 0, every 0.01 mg/kg increase in Tac dose resulted in an AUC24 increase of 3.59 h·μg/L. Conclusions: This study challenges the general belief that C 0 levels are sufficiently reliable to estimate systemic drug exposure. We demonstrated that patients requiring a relatively high Tac dose to attain therapeutic C 0 levels have higher drug exposure and could therefore potentially be overdosed.